??WHAT??S IN A NAME?? AS THE PRIME SIGNIFIER OF DRAMA ROMEO AND JULIET - Taufiqurrohman Taufiqurrohman (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2016)
This essay has distinguished perspective in its purpose although there are many research on ??What??s in a name??. It tries to identify the prime signifier of drama Romeo and Juliet. There must be one statement could be inferred as the drama??s prime signifier. After being read couple times, the writer concluded that drama Romeo and Juliet??s prime signifier is in popular statement ??What??s in a name??. The inference is based on sign analysis. The conclusion has been got is that ??name? is the index for anything being the obstacles of Romeo and Juliet?? love. This name ignorance was proved by their decision of daring to die. Besides, this statement can be the miniature of all themes talked in the drama.